Emmetropes and myopes differ little in their accommodation dynamics but strongly in their ciliary muscle morphology. (October 2019) - Wagner, Sandra; Zrenner, Eberhart; Strasser, Torsten
Highlights: Ciliary muscle is thinner anteriorly and thicker posteriorly in myopic eyes. Myopic ciliary muscle moves more but thickens less anteriorly than emmetropic one. Linear accommodative ciliary muscle changes only found in myopic eyes. Lens power changes to step pulse are not different between emmetropes and myopes. Smaller anterior muscle thickness changes correlate with larger lens power changes. Abstract: Previous work suggested an association between near vision and myopia. We therefore investigated the accommodation process in emmetropes and myopes regarding morphologic changes of the ciliary muscle (CM) and power changes of the lens for different accommodation demands. The temporal CM of 18 emmetropic and 20 myopic students was imaged via anterior segment optical coherence tomography during far and near accommodation (2.5D, 3D, 4D). Additionally, accommodation dynamics to the stimuli pattern far-near-far (15 s each; 2.5D, 3D, 4D) were recorded with eccentric infrared photorefraction. OCT images were processed using custom-developed software facilitating the analysis of selective CM thickness (CMT) readings and CMT profiles. Anterior CMT readings were significantly smaller in myopes. Starting at 1.4 mm posterior to the scleral spur (SP), myopic CM became thicker than emmetropic. Anterior CMT changes (ΔCMT) continuously increased with accommodation demand in myopes while emmetropic ΔCMT only increased from 2.5D to 3D. Compared to emmetropes, myopes showed smaller ΔCMT but increased CM movement relative to SP. There were no significant differences between the groups for accommodation changes from far to near vision and vice versa, velocity, microfluctuations, power spectra or lag of accommodation. At 4 D, larger ΔCMT were associated with lower lens changes for disaccommodation. While CM shape, movement, and thickness showed distinct differences depending on refractive error, emmetropes and myopes did not differ in their dynamic accommodation. Further analysis is necessary to evaluate whether the CM's anatomical shape or predispositions in its intramuscular constituents are causative factors in myopigenesis.